2014
DOI: 10.1242/dev.105346
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic specification of primordial germ cells from mesoderm precursors in axolotl embryos

Abstract: A common feature of development in most vertebrate models is the early segregation of the germ line from the soma. For example, in Xenopus and zebrafish embryos primordial germ cells (PGCs) are specified by germ plasm that is inherited from the egg; in mice, Blimp1 expression in the epiblast mediates the commitment of cells to the germ line. How these disparate mechanisms of PGC specification evolved is unknown. Here, in order to identify the ancestral mechanism of PGC specification in vertebrates, we studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 69 publications
1
79
0
Order By: Relevance
“…PGC transplantation has also been demonstrated in several of these species. For example, transplantation of ventral marginal zone between early gastrula stage embryos in caudate amphibians (salamanders and newts) such as the Mexican axolotl Amblystoma mexicanum results in transfer of the germline between animals (Nieuwkoop, 1947;Smith, 1964;Chatfield et al, 2014). Leapfrogging might also be viable in birds.…”
Section: Factors Influencing Successful Leapfroggingmentioning
confidence: 99%
“…PGC transplantation has also been demonstrated in several of these species. For example, transplantation of ventral marginal zone between early gastrula stage embryos in caudate amphibians (salamanders and newts) such as the Mexican axolotl Amblystoma mexicanum results in transfer of the germline between animals (Nieuwkoop, 1947;Smith, 1964;Chatfield et al, 2014). Leapfrogging might also be viable in birds.…”
Section: Factors Influencing Successful Leapfroggingmentioning
confidence: 99%
“…Blimp-1 orthologs have been identified in many bilaterian animals, including D. melanogaster (Ng et al, 2006;Agawa et al, 2007;Akagi and Ueda, 2011), rabbit (Hopf et al, 2011), D. rerio (Baxendale et al, 2004;Wilm and Solnica-Krezel, 2005), X. laevis (de Souza et al, 1999), salamander (Chatfield et al, 2014), Gallus gallus (Wan et al, 2014), lamprey (Nikitina et al, 2011), sea star (Hinman and Davidson, 2003;Fresques et al, 2014) and sea urchin (Wang et al, 1996;Livi and Davidson, 2006;Fresques et al, 2014). Consistent with evidence from mice, Blimp-1 is widely expressed in a variety of endodermal and/or mesodermal tissues in these animals.…”
Section: Introductionmentioning
confidence: 66%
“…The other mechanism is termed "induced" and here the PGCs are determined later in development in response to a cascade of inducing signals and gene expression [25]. Previous work by Johnson et al [26]; Crother et al [6 , 21] has shown that groups that exhibit the determinative mode are significantly more species rich in general and are always more species rich than their sister clade with the induced mode.…”
Section: A Biological Example Of Evolvability: Primordial Germ Cell Dmentioning
confidence: 99%
“…The explicit molecular developmental pathways that are thought to function as constraint or release have been characterized and reviewed by Chatfield et al [25] and Johnson and Alberio [16]. As a constraint release, it has been argued that this increases the opportunities for the development of evolutionary novelties, some of which become key innovations that enhance speciation rates.…”
Section: A Biological Example Of Evolvability: Primordial Germ Cell Dmentioning
confidence: 99%